2021
DOI: 10.3389/fbioe.2020.621431
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Streptomyces nodosus Mutant With a High-Yield Amphotericin B

Abstract: Antibiotics play an important role in human health. Most antibiotics are derived from microbial secondary metabolites. Amphotericin is a polyene macrolide antibiotic synthesized by Streptomyces nodosus. S. nodosus ZJB2016050 with high-yield amphotericin B (AmB) was obtained by traditional mutagenesis using S. nodosus ATCC14899 as the original strain. The differences in the characterization of the two strains were found in color, mycelium morphology, and AmB yield. Subsequent comparative transcriptome explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In previous research, the expression levels of some key genes in the glycolysis and precursor metabolism pathways of S. nodosus ZJB2016050 were higher than those of the wild-type S. nodosus ATCC14899 (Huang et al 2021). The accumulation of AmB was the fastest from 24 to 48 h. At 96 h, the yields of S. nodosus ZJB2016050 and S. nodosus ATCC14899 were 9.73 mg/g and 7.5 mg/g, respectively (Fig.…”
Section: Fermentation Comparison Of Different Strainsmentioning
confidence: 76%
“…In previous research, the expression levels of some key genes in the glycolysis and precursor metabolism pathways of S. nodosus ZJB2016050 were higher than those of the wild-type S. nodosus ATCC14899 (Huang et al 2021). The accumulation of AmB was the fastest from 24 to 48 h. At 96 h, the yields of S. nodosus ZJB2016050 and S. nodosus ATCC14899 were 9.73 mg/g and 7.5 mg/g, respectively (Fig.…”
Section: Fermentation Comparison Of Different Strainsmentioning
confidence: 76%
“…Carbohydrates are the main carbon sources in the TCA cycle, and inhibition of them would cause damage to the metabolic pathways. Carbohydrate metabolism is one of the main metabolic pathways and forms of energy supply in fungi, including biochemical pathways for biosynthesis, degradation, interconversion, and energy metabolism [ 20 , 21 ]. Effect of isoxanthohumol on the mycelial metabolism was evaluated ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…SHMT not only plays a significant role in carbon metabolism but also is involved in the biosynthesis of antibiotics, which could be extensively applied in the treatment of cancers and the development of antibiotics ( Wang et al., 2022 ). Comparative transcriptome analysis of Streptomyces nodosus mutants showed that upregulated pyruvate dehydrogenase can accelerate the consumption of glucose and has great effects on the accumulation of precursors, in which antibiotics are derived from microbial secondary metabolites ( Huang et al., 2021 ). A previous report showed that intermediary metabolism and respiration by DLD were affected by ethambutol and could be explored as additional drug targets ( Ghiraldi-Lopes et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…From red to green (score 0-2), it means the Domain (P<0.05) -log10(Fisher's exact p value). of precursors, in which antibiotics are derived from microbial secondary metabolites (Huang et al, 2021). A previous report showed that intermediary metabolism and respiration by DLD were affected by ethambutol and could be explored as additional drug targets (Ghiraldi-Lopes et al, 2019).…”
Section: Discussionmentioning
confidence: 99%